TOLERABILITY OF VARIOUS ANTIHYPERTENSIVE COMBINATIONS - S. V. Malchikova; E. I. Tarlovskaya (Столичная издательская компания, 2016)
Aim. To compare tolerability of various antihypertensive combinations in patients with arterial hypertension (HT). Material and methods. 140 patients with HT with history of non-effective antihypertensive therapy were randomized in 4 groups, 35 patients in each. Patients of group A received indapamide retard/perindopril; group B - indapamide retard/amlodipine; group C - amlodipine/lisinopril; group D - amlodipine/bisoprolol. Therapy duration was 12 weeks. Results. 28 (20%) patients dropped out of the study. All antihypertensive combinations significantly decreased blood pressure level. Patients of group A did not stop therapy because of adverse events. 6 (17,1%) dropped out of the study because of ineffective therapy in maximal doses and therapy rejection. Palpitation was a reason of drug withdrawal in 3 (8,6%) of 8 (22,9%) dropped patients of group B. Low limb edema was a reason of drug withdrawal in 4 (11,4%) of 8 (22,9%) dropped patients of group D. Cough was a reason of drug withdrawal in 4 (11,4%) of 5 dropped patients of group C. Dose reduction was needed in some patients of all groups because of hypotension. Conclusion. The adverse events were observed in 25% of patients during 12 weeks of therapy. The patients received indapamide retard/amlodipine and amlodipine/bisoprolol had the highest rate of drug withdrawal because of adverse events. Low limb edema, cough and palpitation were the most frequent adverse events needed therapy withdrawal.